2015
DOI: 10.3892/br.2015.547
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of melatonin and genistein on radiation-induced nephrotoxicity: Results of an experimental study

Abstract: The aim of the present study was to compare the effects of melatonin and genistein on radiation-induced nephrotoxicity (RIN). A total of 70 Swiss Albino mice were divided into 7 groups. Five control groups were defined, which were sham irradiation (C, G1), radiation therapy only (RT, G2), melatonin (M, G3), genistein (G, G4) and polyethylene glycol-400 (G5), respectively. The co-treatment groups were the RT plus melatonin (RT+M, G6) and RT plus genistein (RT+G, G7) groups. Irradiation was applied using a cobal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Melatonin is a potent free radical scavenger with anti-inflammation. The supplementation of genistein and melatonin prior to irradiation protects against nephrotoxicity in mice (Canyilmaz et al, 2016 ).…”
Section: Capacity To Relief Nephrotoxicitymentioning
confidence: 99%
“…Melatonin is a potent free radical scavenger with anti-inflammation. The supplementation of genistein and melatonin prior to irradiation protects against nephrotoxicity in mice (Canyilmaz et al, 2016 ).…”
Section: Capacity To Relief Nephrotoxicitymentioning
confidence: 99%
“…Several in vitro and in vivo studies have investigated the radioprotective effects of melatonin. Animal studies were conducted for various organs such as lung, heart, kidney, liver, gastrointestinal system, skin, testes, lenses, spinal cord and others [183][184][185][186][187][188][189][190][191]. Although the clinical applications for possible radioprotection of melatonin have suffered limitations, some have shown promising results.…”
Section: Melatoninmentioning
confidence: 99%
“…Genistein has been reported to protect against I/R-induced cerebral injury in the rat [ 20 ], and it has a protective role on I/R-induced small intestine injury [ 21 ]. Additionally, Canyilmaz, E. et al demonstrated that the administration of genistein protects mice against radiation-induced nephrotoxicity [ 22 ]. It is of particular relevance that the physiological activity of genistein as a phytoestrogen is closely related to SIRT1 activity [ 23 ].…”
Section: Introductionmentioning
confidence: 99%